Unmasking hemoglobin Köln: a rare cause of discrepancies between pulse oximetry and arterial oxygen saturation—a case report - Alshurafa, Awni; Elsabagh, Ahmed; Obaid, Koutaibah Rida; Elhaji, Youssef; Yassin, Mohamed A. (Frontiers in Medicine, 2024)
Discrepancies between pulse oximetry and arterial oxygen saturation can pose challenges in clinical assessment. Possible underlying causes include poor peripheral perfusion, skin pigmentation, motion artifacts, and conditions like unstable hemoglobin and methemoglobinemia. Unstable hemoglobin variants, such as hemoglobin Köln, are rare inherited mutations affecting globin genes, potentially disrupting the folding, assembly, or interactions among subunits in globin molecules and the essential interactions between heme and globin for oxygen-binding properties. In this case report, we present the case of a 44-yearold Arabic woman who underwent extensive investigations due to disparities in pulse oximetry and arterial oxygen saturation, ultimately leading to the diagnosis of the unstable hemoglobin variant, hemoglobin Köln.